Word Production (Al-TawlÄ«d Al-LuÄ¡awy) in Arabic: Causes and Types - Uki Sukiman (Indonesian Journal of Arabic Studies, 2021)
Word Production (Called in Arabic by Al-TawlÄ«d Al-LuÄ¡awy) which means inventing new words is one of development of language phenomenon that happens in any languages including Arabic. This phenomenon is a demand of condition that one language is not capable of expressing ideas and emotions and has something to do with communication with non-speaker or other languages. Thus, a language can influence and be influenced. This paper tried to uncover reasons and theories using comparative study so that it is clear for Arabic language researchers to use tawlid in their research. The writer found eight reasons why neology emerged, which are development of civilization, friction between Arab and Non-Arab, administration system after Islamic expansion, translation process from Greek into Arabic, social and political demands, the beauty of expression, and inventing new scientific terms, while Ibrahim Murad stated five theories about neology: phonetic neology, morphological neology, semantic neology, spontaneous neology, and borrowing neology; as Nasruddin suggested five theories such as transfer of meaning, derivation, derivation from Arabization (muâ€™rab) or loanwords (dakhil), taulid form coinase and structure, metaphor neology, and meaning expansion.Ø§Ù„ØªÙˆÙ„ÙŠØ¯ Ø¨Ù…Ø¹Ù†Ù‰ Ø¥ØØ¯Ø§Ø« ÙƒÙ„Ù…Ø© Ø¬Ø¯ÙŠØ¯Ø©Â  Ù…Ø¸Ù‡Ø± Ù…Ù† Ù…Ø¸Ø§Ù‡Ø± ØªØ·ÙˆØ±Ø§Ù„Ù„ØºØ§Øª Ù…Ù†Ù‡Ø§ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©.ØªÙƒÙˆÙ† Ù‡Ø°Ù‡ Ø§Ù„Ù…Ø¸Ø§Ù‡Ø± Ù…Ù† Ù…ØªØ·Ù„Ø¨Ø§Øª Ø§Ù„Ø£ØÙˆØ§Ù„ Ù…Ù† Ø¹Ø¯Ù… ÙƒÙØ§Ø¦Ø© Ø§Ù„Ù„ØºØ© ÙÙ‰ ØªØ¹Ø¨ÙŠØ± Ø£ÙÙƒØ§Ø± ØµØ§ØØ¨ Ø§Ù„Ù„ØºØ© Ùˆ Ù…Ø´Ø§Ø¹Ø±Ù‡Ù… Ø®Ø§ØµØ© Ùˆ Ù†ØªÙŠØ¬Ø© Ù…Ù† ØªØ¹Ø§Ù…Ù„Ù‡Ù… Ù…Ø¹ Ø§Ù„Ø¢Ø®Ø±ÙŠÙ† ÙØ£Ø«Ø±ÙˆØ§ ÙˆØªØ£Ø«Ù‘Ø±ÙˆØ§. Ø§Ù‡ØªÙ…Ù‘ ÙƒØ«ÙŠØ± Ù…Ù† Ø¹Ù„Ù…Ø§Ø¡ Ø§Ù„Ù„ØºØ© Ø¨Ù‡Ø°Ù‡ Ø§Ù„Ù…Ø¸Ø§Ù‡Ø± Ùˆ Ø¨ØØ«ÙˆØ§ ÙÙ‰ Ø£Ø³Ø¨Ø§Ø¨Ù‡Ø§ Ùˆ Ø¯ÙˆØ§Ø¹Ù‰Ù‡Ø§ Ø¨Ù„ Ø¬Ø¹Ù„ÙˆØ§ Ù‚ÙˆØ§Ø¹Ø¯Ù‡Ø§. ÙÙ‡Ø°Ù‡ Ø§Ù„Ù…Ù‚Ø§Ù„Ø© ØªØ¹Ø±Ø¶ Ø¬Ù‡Ø¯Ù‡Ù… ÙÙ‰ Ù‡Ø°Ø§ Ø§Ù„Ù…Ø¬Ø§Ù„ ÙÙ‰ Ø§ÙƒØªØ´Ø§Ù ØªÙ„Ùƒ Ø£Ø³Ø¨Ø§Ø¨ ÙˆØ§Ù„Ù‚ÙˆØ§Ø¹Ø¯ Ø¨Ù…Ù†Ù‡Ø¬ Ù…Ù‚Ø§Ø±Ù†Ø© ØØªÙ‰ ØªÙƒÙˆÙ† ÙˆØ§Ø¶ØØ© Ù„Ù…ØØ¨Ø¨ÙŠ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ø±Ø§Ø¬ÙŠØ§ Ø§Ø³ØªØ¹Ù…Ø§Ù„Ù‡Ù…Ù… ÙÙ‰ Ø¨ØÙˆØ«Ù‡Ù… Ùˆ Ù…Ù‚Ø§Ù„ØªÙ‡Ù….ÙˆØ¬Ø¯ Ø§Ù„ÙƒØ§ØªØ¨ Ø«Ù…Ø§Ù†Ù‰Ø© Ø£Ø³Ø¨Ø§Ø¨ Ù„Ø¸Ù‡ÙˆØ± Ø§Ù„ØªÙˆÙ„ÙŠØ¯ ÙÙ‰ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© ÙˆÙ‡ÙŠ Ø§Ù„ØªØ·ÙˆØ± Ø§Ù„Ù€ØØ¶Ø§Ø±ÙŠØŒ ÙˆØ§Ù„Ø§ØØªÙƒØ§Ùƒ Ø¨ÙŠÙ† Ø§Ù„Ø¹Ø±Ø¨ Ø§Ù„Ø£Ø¹Ø¬Ù…ØŒ ÙˆØ§Ù„Ù€ØØ§Ø¬Ø© Ø§Ù„Ù€Ù…Ù„ØØ©ØŒ ÙˆØ§Ù„Ù†Ø¸Ø§Ù… Ø§Ù„Ø¥Ø¯Ø§Ø±ÙŠ Ø¹Ù†Ø¯ Ø§Ù„Ø¹Ø±Ø¨ Ø¨Ø¹Ø¯ Ø§Ù„ÙØªÙˆØØ§Øª Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ©ØŒ ÙˆØ¹Ù…Ù„ÙŠØ© ØªØ±Ø¬Ù…Ø© Ø§Ù„Ø¹Ù„ÙˆÙ… Ø§Ù„ÙŠÙˆÙ†Ø§Ù†ÙŠØ© Ø¥Ù„Ù‰ Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ©ØŒ ÙˆØ§Ù„Ø¯Ø¹Ø§ÙŠØ© Ø§Ù„Ø³ÙŠØ§Ø³ÙŠØ© ÙˆØ§Ù„Ø§Ù‚ØªØµØ§Ø¯ÙŠØ©ØŒ ÙˆØ¬Ù…Ø§Ù„ Ø§Ù„ØªØ¹Ø¨ÙŠØ±ØŒ ÙˆÙˆØ¶Ø¹ Ø§Ù„Ù€Ù…ØµØ·Ù„ØØ§Øª Ø§Ù„Ø¹Ù„Ù…ÙŠØ©ÙƒÙ…Ø§ ÙˆØ¬Ø¯ Ø§Ø¨Ø±Ø§Ù‡ÙŠÙ… Ù…Ø±Ø§Ø¯ Ø§Ù„Ø°ÙŠ Ù‚Ø¯Ù… Ø®Ù…Ø³ Ù‚ÙˆØ§Ø¹ÙŠØ¯ ÙŠØ¹Ù†ÙŠ Ø§Ù„ØªÙˆÙ„ÙŠØ¯ Ø§Ù„ØµÙˆØªÙŠØŒ Ø§Ù„ØªÙˆÙ„ÙŠØ¯ Ø§Ù„ØµØ±ÙÙŠØŒ Ø§Ù„ØªÙˆÙ„ÙŠØ¯ Ø§Ù„Ø¯Ù„Ø§Ù„ÙŠØŒ Ø§Ù„ØªÙˆÙ„ÙŠØ¯ Ø¨Ø§Ù„Ø§Ø±ØªØ¬Ø§Ù„ØŒ Ø§Ù„ØªÙˆÙ„ÙŠØ¯ Ø¨Ø§Ù„Ø§Ù†Ù‚Ø±Ø§Ø¶ØÙŠØ« Ù„ÙƒÙ„ Ù…Ù†Ù‡Ø§ ÙØµÙˆÙ„ ÙƒÙ…Ø§ Ù‚Ø¯Ù… Ù†ØµØ± Ø§Ù„Ø¯ÙŠÙ† Ø³Øª Ù‚ÙˆØ§Ø¹ÙŠØ¯ ÙˆÙ‡ÙŠ Ø§Ù†ØªÙ‚Ø§Ù„ Ø§Ù„Ù€Ù…Ø¹Ù†Ù‰ØŒ ÙˆØ§Ù„Ø§Ø´ØªÙ‚Ø§Ù‚ØŒ ÙˆØ§Ù„Ø§Ø´ØªÙ‚Ø§Ù‚ Ù…Ù† Ø§Ù„Ù€Ù…Ø¹Ø±Ø¨ Ø£Ùˆ Ø§Ù„Ø¯Ø®ÙŠÙ„ØŒÙˆØ§Ù„ØªÙˆÙ„ÙŠØ¯ Ø¨Ø§Ù„Ù†ØØª ÙˆØ§Ù„ØªØ±ÙƒÙŠØ¨ØŒÙˆØ§Ù„ØªÙˆÙ„ÙŠØ¯ Ø§Ù„Ù€Ù…Ø¬Ø§Ø²ÙŠØŒ ÙˆØ§Ù„ØªÙˆØ³Ø¹.